Cultism and Islamism as Impediment to the Growth of Christianity in Nigeria (Global Journal of Human-Social Science, 2020)
The paper "Cultism and Islamism as impediment to growth of Christianity" a look at how the continued effect of cultism and Islamism has impeded and is still impeding the growth of Christianity. Cultism has been treated under causes and effects on the youths, society and Christianity while Islamism is treated as the radical arm of Islam and its strategies of impeding Christianity. Suggestions have been made to encourage unity and peaceful existence of Nigerians.
Keywords: cultism; islamism and christianity